Life-giving, caring leadership: He Totara - Baker H; Poskitt J (Cervin Media Ltd on behalf of the New Zealand Principals Federation)
The metaphor of the Totara tree, and te ao Maori, provides New Zealand primary school leadership with an inspiring, life-giving perspective on leadership.
Keywords: leadership; schools; New Zealand